RETRACTED: Impact of entrance angle of rectangular openings of centrifugal multivortex device on its classification efficiency - Muginov Arslan; Popkova Oksana; Antonov Maksim; Voronina Lenura; Kuznetsov Maxim (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001